Qualidade ambiental urbana (IQAU) de bairros localizados às margens do rio Sergipe no município de Aracaju/SE - Silva, André Vinícius Bezerra de Andrade (2020)
Coastal and estuarine environments have too much importance to the society around them. In this sense, the development of studies aimed at these spaces must reverberate their real value. The environmental quality in urban areas can be assessed at several levels from complex estimative models. Therefore, the present study aimed, in general, to analyze the environmental quality of neighborhoods located on the banks of the Sergipe River in the municipality of Aracaju/SE. For that, we used the matrix of indicators based on the conceptual framework Pressure-State-Response (P-S-R) proposed by the Organization for Economic Cooperation and Development (OECD). The matrix was composed of 18 indicators distributed in three categories (Public spaces, Basic sanitation and Land use / occupation) and all class indicators were fed with secondary information from the responsible institutions. In a complementary way to the study, field visits were made in the public spaces of the spatial cutout and the information related to the vegetation cover was processed through the Geographic Information System QuantumGIS v. 3.2.2., with the purpose of obtaining the Urban Environmental Quality Index (UEQI), which seeks to measure the level of environmental quality in a locality, which directly interferes with the quality of life of the population. The UEQI was calculated based on the selection of 5 indicators (Sewage, Water supply, Urban cleaning, Pavement of roads and Vegetation cover) from the matrix. Given the above, it was noted that the waterproofing of roads and public squares in the spatial area is notorious, which leads to changes in the temperature of living spaces and in the difficulty of rainwater drainage. An interesting observation to be taken into account, concerns the small volume of sewage collected by the sanitation company when compared to the volume of water that reaches homes. Despite the problem of basic sanitation, the study showed that only one neighborhood has the percentage of vegetation coverage within the established standards. The indicators used here are associated with urban infrastructure issues directly linked to quality of life and in turn human and environmental health, so it is hoped that the results shown here can support in decision making as well as for replication in conducting future research.